Comparative study of hydroxyapatite coatings obtained by Sol-Gel and electrophoresis on titanium sheets - Peón Avés,Eduardo (2007)
A comparative study of two coating methods on titanium (Ti) substrates, sol-gel and electrophoresis processes, was performed. Before coating, two different surface treatments were employed. The hydroxyapatite (HA) powder were characterized by infrared spectroscopy (FTIR) and X-ray diffraction (XRD) while coated samples were examined by using scanning electron microscopy (SEM) with energy dispersive spectroscopy (EDS). Both techniques seem to be suitable to coat Ti. A previous surface treatment on metallic titanium seems to be fundamental to enhance coat uniformity and adhesion that was estimated by the adhesive tape test. The decrease in calcination temperature did not affect the coating adhesion.